Populations of Stored Product Mite Tyrophagus putrescentiae Differ in Their Bacterial Communities - Erban, Tomas; Klimov, Pavel B.; Smrz, Jaroslav; Phillips, Thomas W.; Nesvorna, Marta; Kopecky, Jan; Hubert, Jan (Frontiers in Microbiology, 2016)
Background: Tyrophagus putrescentiae colonizes different human-related habitats and feeds on various post-harvest foods. The microbiota acquired by these mites can influence the nutritional plasticity in different populations. We compared the bacterial communities of five populations of T. putrescentiae and one mixed population of T. putrescentiae and T. fanetzhangorum collected from different habitats. Material: The bacterial communities of the six mite populations from different habitats and diets were compared by Sanger sequencing of cloned 16S rRNA obtained from amplification with universal eubacterial primers and using bacterial taxon-specific primers on the samples of adults/juveniles or eggs. Microscopic techniques were used to localize bacteria in food boli and mite bodies. The morphological determination of the mite populations was confirmed by analyses of CO1 and ITS fragment genes. Results: The following symbiotic bacteria were found in compared mite populations: Wolbachia (2 populations), Cardinium (5 populations), Bartonella-like (5 populations), Blattabacterium-like symbiont (3 populations) and Solitalea-like (6 populations). From 35 identified OTUs97, only Solitalea was identifed in all populations. The next most frequent and abundant sequences were Bacillus, Moraxella, Staphylococcus, Kocuria and Microbacterium. We suggest that some bacterial species may occasionally be ingested with food. The bacteriocytes were observed in some individuals in all mite populations. Bacteria were not visualized in food boli by staining, but bacteria were found by histological means in ovaria of Wolbachia-infested populations. Conclusion: The presence of Blattabacterium-like, Cardinium, Wolbachia and Solitalea-like in the eggs of T. putrescentiae indicates mother to offspring (vertical) transmission. Results of this study indicate that diet and habitats influence not only the ingested bacteria but also the symbiotic bacteria of T. putrescentiae.